Evaluation of Lacquered Tinplate Corrosion in Canned Food through Characterization by using SEM & EDS Technique - Dey, Sourajyoti; Mahesh Kumar Agraw, Dr. (International Journal of Engineering and Technology, 2018)
Investigation of tinplate corrosion occurs in the interior of Cans containing food products due to electrochemical reactions. This changing the organoleptic properties of food stuff and produced toxicological problems. To investigate corrosion effect, lacquer adhesion failure of tinplate containers was evaluated with Scan Electron Microscope (SEM) along with Energy Dispersive X-ray spectroscopy (EDS) technique. This technique plays a vital role to investigate the reason of corrosion occurs in cans (container) like stress corrosion in the pack of fish and potatoes, pitting corrosion in the pack of light colored fruits and failure due to lacquer defects. Support of analytical methods may be also required to establish the failure.
Keywords: Tinplate; Lacquer; Scan Electron Microscope; Dispersive X-ray Spectroscopy; Corrosion